BUMDES MITRA JAYA MANDIRI BERPERAN DALAM MENINGKATKAN PARTISIPASI MASYARAKAT MENUJU DESA MANDIRI - Dasri Mulyadi (Jurnal Ilmiah Cano Ekonomos, 2023)
This study aims to determine the role of BUMDes Mitra Jaya Mandiri in increasing village community participation, the role of BUMDes in realizing an independent village, policies developed to support community participation towards an independent village. The research method used is descriptive with data collection techniques including in-depth interviews, observation, and documentation. Data analysis techniques are descriptive quantitative and descriptive qualitative. The results of the study show that the role of BUMDes Sinar Mulya is in increasing community participation through training, outreach and coaching, creating jobs for the community and fostering community business activities. The role of BUMDes in realizing an independent village is to improve community welfare through employment, grow community economic activities, provide easy access to business, and increase village original income (PADes). The policies developed to support community participation towards an independent Village are coordination with the BPD and the Village Government supervising the management of BUMDes, cooperation with the regional government and BUMDes business partners.